Principles of Auditing and Other Assurance Services - Whittington O.Ray (Mc Graw Hill, 2008)
Whittington/Pany’s Principles of Auditing, is a market leader in the auditing discipline. Until October 2002, Ray Whittington was a member of the Audit Standards Board and prior to Ray being on the ASB, Kurt Pany was on the board. This has had a major impact on this revision of the text as Whittington has been involved in the audit standards creation process.